Black soyabean seed coat extract regulates iron metabolism by inhibiting the expression of hepcidin. Issue 7 (14th April 2014) - Mu, Mingdao; Wu, Aimin; An, Peng; Du, Xiaoli; Wu, Qian; Shen, Xiaoyun; Wang, Fudi
<x content-type="archive" xml:space="preserve">Abstract</x> Hepcidin, a key regulator of Fe homeostasis, is an ideal drug target for treating patients with Fe disorders such as haemochromatosis, anaemia of chronic inflammation and Fe-deficiency anaemia. However, whether (and how) traditional Chinese black foods (e.g. black soyabeans) target hepcidin and improve Fe-deficiency anaemia remains unclear. Herein, we report that black soyabean seed coat extract (BSSCE) can potently inhibit the in vitro and in vivo expression of hepcidin. In the present study, in cells treated with 200 μg/ml BSSCE, hepcidin expression was found to be reduced to only 6 % of the control levels (P< 0·01). An AIN-76A diet containing 2 % BSSCE was fed to 8-week-old male C57BL/6 mice for 0, 1, 7, 15 or 30 d; importantly, compared with the day 0 group, the day 7 group exhibited nearly a 50 % decrease in hepatic hepcidin expression (P< 0·01), a 35 % decrease in splenic Fe concentrations (P< 0·05) and a 135 % increase in serum Fe concentrations (P< 0·05). Mechanistically, the effect of BSSCE on hepcidin expression was mediated via a reduction in the phosphorylation levels of mothers against decapentaplegic homolog proteins (Smad)1/5/8. Consequently, the mice in the day 30 group exhibited large increases in erythrocyte counts (111 % v. day 0, P< 0·01), Hb concentrations (109 %, P< 0·01) and haematocrit values (108 %, P< 0·01). In conclusion, these results indicate that black soyabean extract regulates Fe metabolism by inhibiting the expression of hepcidin. This finding can be used to optimise the intervention of patients with hepcidin-related diseases, including Fe-deficiency anaemia.